The Interplay Between Quality of Life and Resilience Factors in Later Life: A Network Analysis - Brinkhof, Lotte P.; Huth, Karoline B. S.; Murre, Jaap M. J.; de Wit, Sanne; Krugers, Harm J.; Ridderinkhof, K. Richard (Frontiers in Psychology, 2021)
Age-related challenges and transitions can have considerable social, psychological, and physical consequences that may lead to significant changes in quality of life (QoL). As such, maintaining high levels of QoL in later life may crucially depend on the ability to demonstrate resilience (i.e., successful adaptation to late-life challenges). The current study set out to explore the interplay between several resilience factors, and how these contribute to the realization and maintenance of (different facets of) QoL. Based on previous work, we identified behavioral coping, positive appraisal, self-management ability, and physical activity as key resilience factors. Their interplay with (various facets of) QoL, as measured with the WHOQOL-OLD, was established through network analysis. In a sample of community-dwelling older adults (55+; N = 1392), we found that QoL was most strongly (and directly) related to positive appraisal style and self-management ability. Among those, taking care of multifunctional resources (i.e., yielding various benefits at the same time) seemed to be crucial. It connected directly to “satisfaction with past, present, and future activities”, a key facet of QoL with strong interconnections to other QoL facets. Our analysis also identified resilience factor(s) with the potential to promote QoL when targeted by training, intervention or other experimental manipulation. The appropriate set of resilience factors to manipulate may depend on the goal and/or facet of QoL that one aims to improve.